Pengaruh Perlakuan Panas Terhadap Struktur Mikro Logam St 60 - Rina Dwi Yani; Tri Pratomo; Hendro Cahyono (Semesta Teknika, 2008)
This research aim to know the transformation of microstructure and it influence to ST 60 when its heated by heat treatment process. Specimen heated and arrested at temperature 800°C during 30 minutes, then is cooled with water coolant. Hardness of test piece is measured [by] before and after heat treatment by using method Rockwell C. Microstructure of metal photograph take by using special camera, and it presenting in millimeter block to calculate ferrite and pearlite content percentage. Result of research indicates that heat treatment to metal ST 60 causing microstructure change and percentage of ferrite was increase, directly causes material hardness value  increase too.